6200 years of human activities and environmental change in the northern central Alps - Scheffer, Clemens von; Lange, Annika; De Vleeschouwer, François; Schrautzer, Joachim; Unkel, Ingmar (Quaternary science journal, 2019)
In this study, we combine erosion and anthropogenic proxies (Ti, Pb) from calibrated portable XRF with pollen and radiocarbon chronologies in peat from mires of the Kleinwalser Valley (Kleinwalsertal, Vorarlberg, Austria) to reconstruct palaeoenvironmental change and human impact in the northern central Alps. Favoured by a wetter climate, two analysed mires formed 6200 years ago in a densely forested valley. Landscape opening suggests that the first anthropogenic impact emerged around 5700 to 5300 cal BP. Contemporaneously, lead enrichment factors (Pb EFs) indicate metallurgical activities, predating the earliest archaeological evidence in the region. Pollen and erosion proxies show that large-scale deforestation and land use by agro-pastoralists took place from the mid- to late Bronze Age (3500 to 2800 cal BP). This period was directly followed by a prominent peak in Pb EF, pointing to metallurgical activities again. After 200 cal CE, a rising human impact was interrupted by climatic deteriorations in the first half of the 6th century CE, probably linked to the Late Antique Little Ice Age. The use of the characteristic Pb EF pattern of modern pollution as a time marker allows us to draw conclusions about the last centuries. These saw the influence of the Walser people, arriving in the valley after 1300 cal CE. Later, the beginning of tourism is reflected in increased erosion signals after 1950 cal CE. Our study demonstrates that prehistoric humans were intensively shaping the Kleinwalser Valley's landscape, well before the arrival of the Walser people. It also demonstrates the importance of palaeoenvironmental multiproxy studies to fill knowledge gaps where archaeological evidence is lacking.
Gesehen am 19.02.2025